Idee i ideaty - Michał Heller; Janusz Mączka (Zagadnienia Filozoficzne w Nauce, 2022)
The original view of Joseph Życiński, presented in his book The Structure of the Metascientific Revolution (1988), boils down to the observation that almost before our eyes a great revolution took place, not in science, but in the philosophy of science, that is the meta-scientific revolution. His concept of the meta-scientific revolution grew out of his fascination with the revolution that took place in the foundations of mathematics in the first decades of the twentieth century. Whether a change in science deserves to be called a revolution is determined by whether the transformations it underwent also reached the meta-level. The set of presuppositions underlying transformations on the meta-level Życiński calls ideata. One of the aims of this article is to critically reconstruct the meaning of this term.